Assessment of location and anatomical characteristics of lingual foramen using cone beam computed tomography - Veličković Stefan; Matijević Stevo; Jovičić Bojan; Bubalo Marija; Stevanović Momir; Vasović Miroslav (Vojnosanitetski Pregled)
Background/Aim. A lingual foramen (LF) is a small opening on the lingual surface of the mandible, most frequently located in the middle of the anterior part of the mandible, and shows significant variations in its location, size, and number. The aim of this study was to assess the location and anatomical characteristics of LF using cone beam computed tomography (CBCT). Methods. The research was designed as a retrospective study in which 99 CBCT scans were analyzed. The analysis covered the number of LF, their location concerning the teeth and the mandibular region itself, diameter, distance from the alveolar ridge crest, distance from the inferior border of the mandible, distance from the tooth apex, and position in relation to the tooth apex. Results. The average frequency of LF per patient was 2.4 ± 1.2. The largest number of LF were localized in the region of lower central incisors. Out of the total number of LF, 82.5% belonged to median LF, while 17.5% belonged to lateral LF. In 63.2% of cases, LF had a diameter of ≤ 1 mm, whereas, in 98.3% of cases, it was localized below the tooth apex. There was a statistically significant difference in the distance of LF from the alveolar ridge crest and the LF diameter in relation to gender (p = 0.019; p = 0.008). Conclusion. LF can be reliably localized and visualized using CBCT. It is recommended that CBCT scanning of the mandible be used while planning an oral surgical procedure and implant placement in order to prevent injuries of the neurovascular bundle, which passes through LF.